Price Elasticity of Sectoral Lending in Nepal - Chaudhary, Shashi Kant; Pandit, Kiran Raj (NRB Economic Review, 2019)
During 2015 to 2019, there was a significant upsurge observed in the lending rate in Nepalese credit market. Interestingly, the lending amount also went up significantly in this period showing an anomalous relationship between lending and lending rate. This paper is an attempt to analyse this observed anomaly. We have estimated and examined the degree of elasticity of sectoral lending with lending rate in Nepalese context undertaking panel regression analysis covering all 28 commercial banks in operation in Nepal till mid-July 2019.The results show a positive and inelastic relationship to exist between sectoral lending and lending rate during the study period despite decreasing Herfindahl-Hirschman index in the same period, which means that level of competition is increasing in Nepalese banking industry. Our scenario analysis indicates syphoning of funds, and the changed role of bankers as major causes for this anomalous relationship.